The Impact of Distance Learning on Students’ Psychology During The Covid-19 Pandemic - Sri Wulan Lindasari; Reni Nuryani; Nunung Siti Sukaesih (Journal of Nursing Care, 2021)
The education sector is one of those affected by the Covid 19 pandemic. In order to stop the spread of Covid 19, the government has implemented a distance learning process. The problem of distance learning is that students feel bored at home, signal limitations and piles of assignments. With this, it can lead to some psychological problems that occur in students such as anxiety, stress or depression. The purpose of this study was to determine the impact of distance learning on students' psychology during the Covid 19 pandemic in Sumedang. The type of research used is descriptive quantitative with a sample size of 220 junior and senior high school students. The sampling technique used is simple random sampling. The data collection tool used is the DASS 21 questionnaire consisting of 21 questions about anxiety, stress and depression. The data collection process is carried out using the Google form platform. The data were analyzed using a frequency distribution. The results showed (42.27%) experienced anxiety, (44.56%) experienced stress and (23.18%) experienced depression. The most psychological problem experienced by students during distance learning is stress. Therefore, it is necessary to increase coaching and counseling programs to overcome anxiety, stress and depression in the face of distance learning